Aplicación de una auditoría de gestión en la cooperativa Ambato ubicado en el cantón de Latacunga provincia de Cotopaxi durante el período 01 de enero al 31 de diciembre del 2012 - Chiliquinga Cuyachamin, Nelly Isabel (2015)
The success or failure of a company is related to good or bad administration, especially when it comes to organizations where it is essential to providing good services. In this case study was conducted to develop a Management Audit of Cooperative Savings and Credit Ambato branch Latacunga in the area of credit, cash, customer primarily to evaluate the processes applied through the verification of existing procedures, reviewing compliance with legal regulations and internal control assessment, taking overall objective an analysis of the efficiency, effectiveness and economy in the use of human, material and financial resources. Could be detected several shortcomings that hindered development….